Synthesis and antibacterial study of sulfobetaine/quaternary ammonium-modified star-shaped poly[2-(dimethylamino)ethyl methacrylate]-based copolymers with an inorganic core - Pu, Yuji (2018)
Star polymers with poly[2-(dimethylamino)ethyl methacrylate] as the arms and POSS as the core (POSS-g-PDMA) were synthesized by atom transfer radical polymerization (ATRP). The effect of molecular weight on the antibacterial activity was studied and lower molecular weight POSS-g-PDMA has better bactericidal activity as measured by the minimum inhibition concentration. POSS-g-PDMA was further modified by various techniques to increase hydrophilicity in attempting to improve their antifouling activity without compromising bactericidal activity. POSS-g-PDMA was quaternized to different degrees and the antibacterial activities of the obtained quaternary polymers were studied; the antibacterial activity decreased as the degree of quaternization increased. Finally, cationic-zwitterionic polymers with both random and block structures, where PDMA and poly(sulfobetaine) were cationic and zwitterionic blocks respectively, were synthesized. The random cationic-zwitterionic polymers showed poor antibacterial activity while the block polymers retained the antibacterial activity of the pristine POSS-g-PDMA. The block copolymers of POSS-g-(PDMA-b-polysulfobetaine) showed enhanced antifouling property and serum stability as seen by their nanoparticle size stability in the presence of serum and reduced red blood cell aggregation. The antibacterial kinetics showed that E. coli can be killed within 30 min by both random and block polymers. Finally, block polymers showed low toxicity to zebrafish embryo and could be potentially used in aquaculture antibacterial applications.